Gospel women and the long ending of Mark - Lyons-Pardue, Kara 1980- ([London, England] T & T Clark, 2020)
"Kara Lyons-Pardue examines the issue of the ending of the gospel of Mark, showing how the later additions to the text function as early receptions of the original gospel tradition providing an ancient "fix" to the problem of the ending in which the women flee the tomb in terror and silence. Lyons-Pardue suggests that the long ending functions canonically, smoothing out the "problem" of 16:8 in ways that support the nascent four-gospel canon. Lyons-Pardue argues that the long ending represents an ancient reception of the preceding gospel that continues to the unique portrait of discipleship that is characteristically Markan. Mary Magdalene forms the renewed paradigm of an unlikely person or outsider, here a woman, being the one to "go and tell" the good news. This pattern is then projected onto all disciples who are called to proclaim the news to the entire created order (16:15)."--
List of Tables Abbreviations List of Abbreviations of Ancient Sources Acknowledgements Abbreviations Introduction -- 1. Scholarly Inquiry into the Long Ending as a Conclusion to Mark's Gospel -- 2. Mary Magdalene in the Long Ending and Mark 3. Unfaithful Disciples in the Long Ending and Mark 4. Being Disciples Like Mary Magdalene: Implications of the Long Ending's Reading of Mark Appendix: The Many Endings to Mark's Gospel: Introductions, Text, and Translations Bibliography Author Index Ancient Index Subject Index.
Includes bibliographical references and index
Keywords: Bible -- Criticism, interpretation, etc; Bible; Women in the Bible; Biblical studies & exegesis; Criticism, interpretation, etc; Electronic books